2016
DOI: 10.1007/s13224-016-0912-0
|View full text |Cite
|
Sign up to set email alerts
|

Admission Cardiotocography: A Predictor of Neonatal Outcome

Abstract: Background Screening for fetal distress is a big challenge for obstetricians. Labor admission test by cardiotocography (CTG) can be utilized to differentiate between mothers, in whom continuous fetal monitoring is needed and those who can be managed by intermittent auscultation. Admission CTG is commonly used screening test which aims to identify on admission to the delivery unit the fetus at increased risk of intrapartum hypoxia. We conducted a study to evaluate the efficacy of CTG in low-and high-risk women.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 7 publications
2
21
0
Order By: Relevance
“…In our study the major age group was 20 -30 years (62%) followed by 30 -40 years (38%). This is similar to study done by Kansal et al in which 44% of patients belonged to age group of 26 -30 year [4,5,8,[9][10][11] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study the major age group was 20 -30 years (62%) followed by 30 -40 years (38%). This is similar to study done by Kansal et al in which 44% of patients belonged to age group of 26 -30 year [4,5,8,[9][10][11] .…”
Section: Discussionsupporting
confidence: 91%
“…Some Feotuses are already in stress at the time of admission to labour ward [4] . Thus admission CTG detects the ability of foetus to withstand the stress of labour [5] . This is also known as Labour Admission test first described by Ingemarsson et al [6] , particularly useful in a busy labour ward where high risk patients are detected at the time of admission, It is a short electronic Fetal monitoring for 20minutes,, in which record of fetal heart and uterine activities monitored.…”
Section: Introductionmentioning
confidence: 99%
“…In study by Bhartiya et al, 72 (36%) were low-risk and 128 (64 %) were high-risk women. 7 Rajalekshmi et al in their study had 267/400 (66.755) low risk cases whereas 133 (33.25%) high risk case. 5 In a study conducted on 201 high risk cases by Gupta et al, similar results as ours was found 63.2% had reactive CTG pattern and 36.8% had nonreactive CTG pattern.…”
Section: Resultsmentioning
confidence: 86%
“…The incidence of thick meconium‐stained liquor, admission to NICU and neonatal mortality were also significantly higher in the ominous and equivocal groups compared with the reactive ACTG group and operative birth for suspected fetal compromise was required in 5.5% ( n = 8/145) of women in the reactive group compared with 27.8% ( n = 5/18) in the equivocal group and 84.6% ( n = 11/13) of women in the ominous group. Bhartiva et al also report a significant correlation ( P = 0.001) between nonreassuring ACTG and meconium‐stained liquor in low‐risk women, although statistically insignificant correlations were found for low Apgar scores, NICU admission and mortality . Contrastingly, Akhavan et al, in their recent study of 425 pregnant women of whom 142 (33.4%) had abnormal ACTGs, assert that an abnormal ACTG was predictive of caesarean section, intrauterine growth restriction and low Apgar scores (< 7) at birth…”
Section: Discussionmentioning
confidence: 99%